Musicians' Union; as an example of the institutionalization of networks in music - Yıldız, Kıvılcım (My University, 2019)
Musicians1 Unions which are partly autonomous and partly governmental, directed state funds and private sector resources. They aim at emancipating cultural policies from the personal choices of politicians over the use of funds, by means of introducing several arrangements. However, these umbrella institutions, which are responsible from allocation and supervision of funds, do not exist in Turkey. Such a union is clearly necessary in Turkey, to equip the members of the profession with legal and economical power so that they can act jointly, and to be more effective within the society. From this point of view, this paper will attempt to discuss several issues concerning the possible network opportunities of classical music professionals in Turkey.